PENGARUH BUDAYA KERJA, KEPUASAN KERJA DAN FASILITAS KERJA TERHADAP KUALITAS PELAYANAN PT. BORNEO AUTO CEMERLANG CABANG BENGKULU (ISUZU) - Onsardi, Onsardi; Cahyadi, Tirta; Wahyudi, Dedy (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This research aims to find out which factors most dominantly influence service quality. The sample for this research is employees of PT. Borneo Auto Cemerlang Bengkulu Branch (ISUZU). This research used quantitative methods on 35 respondents. The method used in this research is a quantitative method with Multiple Linear Regression analysis using SPSS 24 for Windows. The research results and hypotheses in this study show that the variables of work culture, job satisfaction and work facilities have a partial or simultaneous positive effect on the quality of  service at PT. Borneo Auto Cemerlang Bengkulu Branch (ISUZU). Keywords: Work Culture, Job Satisfaction, Work Facilities and Service Quality.